CLAUSEWITZ AND SANDHURST: OFFICER TRAINING IN BRITAIN - Moorcroft, P.L. (Scientia Militaria - South African Journal of Military Studies, 2012)
The Royal Military Academy, Sandhurst, is the very quintessence of the English establishment.Even now in the latter half of the twentieth centurythe charm - and the irrelevance - of theVictorian Empire still pervades the atmosphere.It all started long before the young Victoriacame to the throne. In fact, in 1798, when ahandsome and ambitious young cavalry colonel bythe name of John Gaspard Le Marchant, a ChannelIslander, started a campaign to establish anofficer training college to improve the professionalstandards of the highly amateurish, albeit largelysuccessful, British Army. The idea soon attractedroyal favour. By 1802, a fashionable architect,and special protege of King George III, acertain Mr Wyatt, had finished his designs forthe buildings. In 1812 the college was openedin its present grounds in Camberley about 40miles from London on the main Southamptonroad.